The Role of Visual Media as a Bridge Between Imagery and Language in the Context of Writing Instruction - Sriwidiastuty, Asi; Supriyanto, Teguh; Sarwi (Proceedings of International Conference on Science, Education, and Technology, 2025)
This study highlights the importance of improving writing skills among elementary school students, particularly considering the persistent challenges many students face in generating ideas and constructing coherent, logical narratives. The primary focus of this research is to examine the role of visual media as a bridge between visual forms and verbal expression in the context of writing instruction. Employing a qualitative descriptive method with an exploratory case study approach, the study involved two teachers and fifth-grade students from SKH 2 KTG and SKH 45 GMK in Central Kalimantan. Data were collected through direct observation, in-depth interviews, and analysis of students' written work. Findings indicate that visual media significantly supports students' cognitive processes, especially in developing ideas, organizing narrative structures sequentially, and reducing affective barriers that often hinder writing. Images were found to serve not only as a stimulus for creativity but also as a tool that connects students’ lived experiences with the narratives they produce. For further development, future research is recommended to explore the cognitive processes involved in transforming visual stimuli into verbal expression and to examine the effectiveness of more dynamic visual media—such as videos or animations—in enhancing students' writing skills. Such strategies are believed to broaden the horizon of understanding regarding adaptive, inclusive, and contextually relevant multimodal learning in contemporary education.